THE ELDERLY DEPENDENCY RATE IN URBAN AREAS OF TRANSYLVANIA REGION BETWEEN 1992 AND 2021 - ȚĂRUȘ, Raisa; DEZSI, Ștefan (Studia Universitatis Babeș-Bolyai Geographia, 2021)
Population ageing becomes a serious issue not only in developed countries, but also in a post-socialist country such as Romania. Nowadays, the demographic tendencies of ageing trends are visible in the demographic dynamics of developed countries, especially in Central and Eastern European Countries in the context of economic growth and population loss. For example, in Romania, it is noticeable in urban areas and rural areas where the demographic trajectories show the presence of a certain demographic phenomenon in age structure of population such as “population ageing”. In the last decades, Romania has entered a period of rapid and dramatic ageing demographic phase. In this respect, first we investigate the phenomenon of population ageing in Transylvania region. Secondly, the paper presents the calculation of elderly dependency rate based on demographic statistical data provided by the National Institute of Statistics. Thirdly, it drives some possible social-economic effects of the progressive process of ageing tendency.